A study of factors that contribute to the long waiting time at General Hospital of Malacca / Siti Nadiah Ab Rahman and Nur Ameera Md Shab - Ab Rahman, Siti Nadiah; Md Shab, Nur Ameera (Faculty of Administrative Science and Policy Studies, 2013)
A study of factors that contribute to the long waiting time at General Hospital of Malacca have been undertaken to seek the perception of outpatient regarding on the long waiting time. The rational of having this study is hospital to improve the efficiency of their service by taking into account on unreasonable waiting consume by the patient before they received a treatment or service. Thus, the result of study will then ease them to make major improvement in a certain part of their performance. For this study, it involve four independent variables that are shortage of worker, lack of facilities, technology and equipment, high workload as well as lack of efficiency and one dependent variable that is long waiting time. A convenience sampling technique were used and about 100 questionnaires were distributed by using selfdistributed method. The questionnaire were distributed at outpatient department of Malacca General Hospital. The research finding shows that shortage of worker, lack of facilities, technology and equipment (r=.237, p<.05 ), shortage of worker (r=.191, p<.05), and lack of efficiency (r=.410, p<.05 ). Lack of efficiency has significance toward long waiting time and the other factors which are the shortage of worker, lack of facilities, technology and equipment and high workload shows less significance result.